Characterization of an ODM Type K Thermocouple for Temperature Measurement Accuracy - Muhammad Dimas Arya; Gelar Aji Auzan Hakim; FELLEZIA RAHEL VIOLETA FELLE (Faraday: Journal of Fundamental Physics, Research, and Applied Science, 2025)
This study characterizes and evaluates the performance of an ODM Type K thermocouple in measuring temperature within the range of 0°C to 100°C under controlled laboratory conditions. The experiment utilized a hot plate as the heat source, with melting ice and boiling water as reference points for 0°C and 100°C, respectively. The thermoelectric voltage generated by the thermocouple was measured using a digital multimeter and compared with readings from an ASTM mercury-in-glass thermometer as a reference. The results showed a strong linear relationship between thermoelectric voltage and temperature, consistent with the Seebeck effect. The average deviation between the thermocouple and the reference thermometer was approximately ±0.3°C, with maximum errors within ±1°C. These findings indicate that the ODM Type K thermocouple demonstrates high accuracy, good linearity, and stability, making it suitable for laboratory and industrial temperature measurement applications.